Rwanda 1994 - Collins, Barrie. author. aut Link
XIV, 272 p.
Keywords: Through a rigorous critique of the dominant narrative of the Rwandan genocide, Collins provides an alternative argument to the debate situating the killings within a historically-specific context and drawing out a dynamic interplay between national and international actors.